Honduras - Debt Management Performance Assessment (DeMPA) - World Bank (Washington, DC, 2022)
The DeMPA is a methodology for assessing public debt management performance through a comprehensive set of indicators spanning the full range of government debt management functions. The DeMPA tool presents the 14 debt performance indicators along with a scoring methodology. The DeMPA tool is complemented by a guide that provides supplemental information for the use of the indicators.